Demographic Characteristics and Clinical Factors of the Patients Suffering from Osteoarthritis of Hand – A Study Done in A Tertiary Specialized Hospital in Bangladesh - Sultan, Md Zobayed; Sharmin, Saida; Sultana, Razia; Tanzil, Merina (Mugda Medical College Journal, 2024)
Background: Osteoarthritis (OA) is one of the most common forms of arthritis. Hand OA is a heterogeneous, age and gender-dependent disorder, occurring more frequently in postmenopausal women over 50 years of age. Objective: This study aims to identify demographic patterns and factors associated with osteoarthritis of the hand among patients attending a tertiary-level hospital in Bangladesh. Methods: This cross-sectional study was done in the Department of Orthopedics, Shaheed Ziaur Rahman Medical College Hospital, Bogura, Bangladesh, between January and December of 2021. A total of 90 patients with OA of hands were included in this study. All patients were selected conveniently and informed written consent of the patients was taken. Participant data were collected through face-to-face interviews using a semi-structured questionnaire. Statistical analyses were done with Statistical Package for Social Science (SPSS) version 25.0. Quantitative variables were analyzed by mean and standard deviation while qualitative variables were summarized by percentage. Results: In this study, the age distribution of the patients ranges from e”40 years to d”75 years irrespective of sex. The mean age of the patients of both sexes was 56.6±8.72 years. Among those 90 patients, 35 persons (38.9%) were male and 55 (61.1%) were female. Most of the patients are housewives 38 (42.22%). Most of the women (87.27%) are menopausal among the total 55 female patients. Only 13 (14.45%) persons had a previous history of a hand injury, and 20 (22.22%) persons had a habit of smoking or previously smokers. Most of the subjects 78 (86.67%) were right-hand dominant and a maximum of 67 (74.45%) persons enrolled in this study showed priority affected CMC1 OA to the dominant hand. Most of them (75.55%) took medications for treatment for arthritis. Conclusion: Our study revealed that osteoarthritis of the hands is predominant in females and affects mostly the right hand. Further high-quality studies examining the risk factors for hand osteoarthritis are needed to replicate these findings and determine modifiable factors in symptomatic patients. Mugda Med Coll J. 2023; 6(2): 77-82